Complex multicusped postcanine teeth from the Lower Triassic of South Africa - Gaetano, Leandro Carlos (2012)
Two incisors and five postcanine teeth of complex crown morphology were found in the lower levels of the Burgersdorp Formation of the Beaufort Group, corresponding to the basal Subzone A of the Cynognathus Assemblage Zone (late Olenekian). All the teeth bear a single root and the postcanines show two rows of mesiodistally aligned cusps and a central basin or groove. Among the postcanines, two general patterns of crown morphology are recognized on the basis of relative length of the cusp rows, number of cusps per row, and width of the central area. Phylogenetic affinities of the described specimens remain unclear, and thus they are regarded as Eucynodontia incertae sedis. However, comparisons with non-mammalian cynodonts with labiolingually expanded postcanines show that they are most similar to those of Aleodon, Candelariodon, and some haramiyids. Many cynodont taxa such as Aleodon, Candelariodon, Cromptodon, haramiyids, and tritylodontids, which are probably not closely related to each other, have labiolingually expanded postcanines with cusps arranged mesiodistally in rows and a central basin; thus pointing to the homoplastic nature of dental morphologies in the cynodont lineage. The teeth presented here are the oldest record of therapsid teeth with crowns having parallel rows of cusps, representing a temporal extension of approximately 10 million years for this crown pattern.